Social media, body image and food choices in healthy young adults: A mixed methods systematic review. Issue 1 (3rd October 2019) - Rounsefell, Kim; Gibson, Simone; McLean, Siân; Blair, Merran; Molenaar, Annika; Brennan, Linda; Truby, Helen; McCaffrey, Tracy A.
Abstract: Aim: Negative body image increases the risk of engaging in unhealthy dieting and disordered eating patterns. This review evaluated the impact of habitual social media engagement or exposure to image‐related content on body image and food choices in healthy young adults (18‐30 years). Methods: A systematic search of six databases of observational literature published 2005‐2019, was conducted (PROSPERO Registration No. CRD42016036588). Inclusion criteria were: studies reporting social media engagement (posting, liking, commenting) or exposure to image‐related content in healthy young adults. Outcomes were: body image (satisfaction or dissatisfaction) and food choices (healthy eating, dieting/restricting, overeating/binging). Two authors independently screened, coded and evaluated studies for methodological quality. Results: Thirty studies were identified (n = 11 125 participants). Quantitative analysis (n = 26) identified social media engagement or exposure to image‐related content was associated with higher body dissatisfaction, dieting/restricting food, overeating, and choosing healthy foods. Qualitative analysis (n = 4) identified five themes: (i) social media encourages comparison between users, (ii) comparisons heighten feelings about the body, (iii) young adults modify their appearance to portray a perceived ideal image, (iv) young adults are aware of social media's impact on body image and food choices, however, (v) external validation via social media is pursued. Most studies (n = 17) controlled for some confounding variables (age, gender, BMI, ethnicity). Conclusions: Social media engagement or exposure to image‐related content may negatively impact body image and food choice in some healthy young adults. Health professionals designing social media campaigns for young adults should consider image‐related content, to not heighten body dissatisfaction.